IL-17C Mitigates Murine Acute Graft-vs.-Host Disease by Promoting Intestinal Barrier Functions and Treg Differentiation - Gong, Huanle; Ma, Shoubao; Liu, Shuangzhu; Liu, Yonghao; Jin, Ziqi; Zhu, Ying; Song, Yuan; Lei, Lei; Hu, Bo; Mei, Yu; Liu, Hong; Liu, Yuejun; et al. (Frontiers in Immunology, 2018)
Acute graft-versus-host disease (aGVHD) is one of the major complications and results in high mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). IL-17C is involved in many inflammatory immune disorders. However, the role of IL-17C in aGVHD remains unknown. Here we demonstrated that IL-17C deficiency in the graft significantly promoted alloreactive T cell responses and induced aggravated aGVHD compared with wildtype donors in a fully MHC-mismatched allo-HSCT model. In contrast, IL-17C overexpression ameliorated aGVHD. IL-17C deficiency increased intestinal epithelial permeability and elevated inflammatory cytokine production, leading to an enhanced aGVHD progression. Tregs was reduced in recipients of IL-17C-/- graft, whilst restored after IL-17C overexpression. Decreased Treg differentiation was abrogated after neutralizing IFN-γ, but not IL-6. Moreover, depletion of Tregs diminished the protective effect of IL-17C. Of note, patients with low IL-17C expression displayed higher aGVHD incidence together with poor overall survival, thereby IL-17C could be an independent risk factor for aGVHD development. Our results are the first demonstrating the protective role of IL-17C in aGVHD by promoting intestinal barrier functions and Treg differentiation in a MHC fully mismatched murine aGVHD model. IL-17C may serve as a novel biomarker and potential therapeutic target for aGVHD.